A note on model selection in (time series) regression models - General-to-specific or specific-to-general? - Helmut Herwartz (Kiel University, Department of Economics, 2007)
The paper provides Monte Carlo evidence on the performance of general-to-specific and specific-to-general selection of explanatory variables in linear (auto)regressions. In small samples the former is markedly inefficient in terms of ex-ante forecasting performance.
Keywords: C22; C51; 330; Model selection; specification testing; Lagrange multiplier tests